The importance of health care among voice student / Josua Eleazar Jalani - Jalani, Josua Eleazar (2014)
This thesis presents the results of The Importance of Health Care among Voice Students in Music Education Departments, Faculty of Music UiTM Shah Alam, or, as suggested by the title. The main hypothesis behind this study is that voice care can give rise to 3 students ability and performance. This thesis comes out after several findings that show the voice students in Music Education Departments ignoring their voice care and influence their performances in Faculty of Music Shah Alam. The dissertation is divided into five chapters, excluding the General Introduction and the General Conclusion. Each chapter deals with a particular aspect of health can. Chapter 1 presents an overview of voice and the health care that supposed to be understand by voice students. Chapter 2 describes about the literature review that been read by the author for source and guiding to complete this thesis, which is important to be guidelines to accomplish this project Methodology is stated in chapter 3 which are included all the maverials and method that used in this thesis and gathered all the result and findings, Chapter 4 contribute all the result and findings that been released by the author. This chapter shows the result that needed by the author to be calculate and conclude as the final findings. By proceeding in this way, the subsequent analyses in chapter 5 are underpinned, not only empirically by the test results but also by the observations presented in earlier chapters. Chapter 5 conclude all the thesis result and suggestion for recommendation that supposed to be done by other researcher.